From Expert Elicitations to Integrated Assessment: Future Prospects of Carbon Capture Technologies - Elena Claire Ricci; Valentina Bosetti; Erin Baker; Karen E. Jenni (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper analyzes the future prospects of carbon capture technologies. The first part of the analysis presents and discusses the results of an expert elicitation survey on a broad range of carbon capture options. The survey collected probabilistic estimates on the future values of energy penalty under three different scenarios of R&D investments and climate policies from twelve leading European experts from both academia and industry. In the second part of the analysis, the elicitation results are used as input to an integrated assessment model. This allows us to evaluate the potentials of success of this technology within a broad mitigation portfolio of options and under different policy assumptions, in an intertemporal optimizing setting. Both parts of the work provide results that are of interest to policy-makers, integrated-assessment and energy modelers.
Keywords: Q5; Q55; 330; Carbon Capture; Expert Elicitation; Integrated Assessment Modeling